Study of Addition Gelatin and Egg White on The Physicochemical and Organoleptic Characteristics of Sawo Kecik Marshmallows and Telang Flower and Determining The Storage Period Using The ESS Method ( Extended Storage Studies ) - Alfiansyah, Romi Angga; Rosida, Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Marshmallow is a confectionery product that has a soft, chewy texture and is white. Problems with a texture that is less soft, less chewy, and less attractive color often arise when processing marshmallows. The addition of butterfly pea flowers can help improve the color, while the use of gelatin and egg whites can be an alternative to improve the texture of marshmallows. This research aimed to determine the best treatment combination between adding gelatin and egg whites to obtain sapodilla marshmallows and butterfly pea flowers with good treatment. This research used a Completely Randomized Design (CRD) with a factorial pattern, two factors, and two replications. Factor 1 is the addition of gelatin (8%; 10%; 12% w/w) and factor 2 is the addition of egg white (4%; 6%; 8% w/w). Data were analyzed using ANOVA and further DMRT tests at the 5% level. The treatment with the addition of 12% gelatin and the addition of 6% egg white was the best treatment which produced sapodilla marshmallows and butterfly pea flowers with characteristic water content values ​​of 47.962% ± 0.2942, ash content of 1.355% ± 0.1972, vitamin content of 16.340 mg/100 g ± 0.1556, reducing sugar content 9.595% ± 0.1768, Aw value 0.468% ± 0.0092, texture 3.975 N ± 0.0495 and organoleptic test color 3.60 (rather dislike), taste 4.04 (normal ), aroma 3.12 (somewhat dislike) and texture 6.12 (like) and antioxidant activity IC50 of 35.52 ppm and has a shelf life of 7 days.